2020
DOI: 10.1371/journal.pone.0235333
|View full text |Cite
|
Sign up to set email alerts
|

Measuring satisfaction with health care services for Vietnamese patients with cardiovascular diseases

Abstract: Patient satisfaction is a useful predictor of adherence and outcomes of cardiovascular diseases (CVDs) treatment. This study explored the satisfaction of Vietnamese CVDs inpatients and outpatients using a scale specifically designed for CVDs patients and examined the factors associated with satisfaction towards CVDs treatment services. Interviews of 600 patients at the Hanoi Heart Hospital were conducted. We developed a measurement scale for both inpatient and outpatient services. Multivariate Tobit regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
7
0
1
Order By: Relevance
“…This study showed that patients with heart disease were more likely to prefer quality health care than healthcare affordability or a short distance to a health facility. This is in agreement with previous studies, which have also documented that chronic heart disease patients are more likely to prefer quality healthcare services 31–33 . Several attributes might influence a patient's preference for quality healthcare services.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study showed that patients with heart disease were more likely to prefer quality health care than healthcare affordability or a short distance to a health facility. This is in agreement with previous studies, which have also documented that chronic heart disease patients are more likely to prefer quality healthcare services 31–33 . Several attributes might influence a patient's preference for quality healthcare services.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with previous studies, which have also documented that chronic heart disease patients are more likely to prefer quality healthcare services. 31 , 32 , 33 Several attributes might influence a patient's preference for quality healthcare services. For instance, heart disease may be associated with both acute episodes and high levels of long‐term adverse events (e.g., mortality and disability).…”
Section: Discussionmentioning
confidence: 99%
“…Another study done in Saudi Arabia had shown that patients, who traveled abroad for renal transplantation, went to Pakistan (49%) followed by the Philippines (28%), Egypt (11%), and the United States (3.2%). 18 Couple of reasons for the Omani patients to travel abroad were revealed in the study including the long waiting time in the local hospitals (52.2%), lack of confidence in the health services provided in Oman (45%), high quality of health care abroad (41%), unavailability of the treatments locally (30.5%), combining treatments with relaxing holidays (11.5%), costcompetitive advantages (10%), and others. In a previous study, Al-Hinai reported that 15% of the participants did not even seek any medical care locally, but rather traveled abroad directly without specific explanations.…”
Section: Resultsmentioning
confidence: 96%
“…Vietnam has made significant progress toward achieving universal health coverage, and 87% of the population is currently covered by national insurance (WHO Representative Office for Vietnam, 2016). Unfortunately, patient evaluations of hospital services have been lower among those using insurance compared with those paying out of pocket (Hwang et al, 2020), which might be associated with patients' hesitation to use insurance. Such differences in service quality depending on the payment method require further investigation.…”
Section: Discussionmentioning
confidence: 99%